MANAGEMENT IN THE OCCUPATIONAL SAFETY AND HEALTH SYSTEM - Đorđević, Violeta; Gordić, Jovan; Krstić, Boro (ACADEMIC REVIEW, 2025)
Management within the occupational safety and health (OSH) system is based on a structured approach to planning, directing and controlling processes to preserve employees' health and safety. This process occurs under specific working conditions and requires continuous adaptation to social, technological, and legislative changes. Management activities involve risk analysis, hazard assessment, and implementing preventive measures by applicable laws and standards. A key role is played by various stakeholders – from institutions and organizations to individuals – whose interaction significantly contributes to the system's overall effectiveness. Of particular importance is the influence of the individual within the OSH system. Every employee, through their behavior, awareness, and sense of responsibility, can directly impact the safety of their colleagues. This influence operates on multiple levels: toward an individual (e.g., mentoring or hazard alerting), within a group (through teamwork and the sharing of best practices) and at the organizational level (by establishing a safety culture within the workplace). In doing so, individual actions contribute not only to personal protection but also to the reinforcement of the broader OSH system. The focus of this paper is to explore the significance of management in the field of occupational safety and health, as well as its impact on the reduction of occupational risks and the improvement of working conditions. The research findings contribute to a deeper understanding of management practices that support a sustainable and resilient employee protection system.